On Fixed Point of Monotone \((α,β)\)-Nonexpansive Mappings in Ordered Hyperbolic Metric Spaces - Dewangan, Kiran (Communications in Mathematics and Applications, 2024)
This paper is concerned with convergence and \(Δ\)-convergence of a sequence generated by Picard-Mann hybrid iteration scheme for monotone \((α,β)\)-nonexpansive type mappings in ordered hyperbolic metric spaces along with some fixed point results. An application in \(L_{1}([0,1])\) space is discussed here.
Keywords: Fixed point; \((α,β)\)-nonexpansive mapping; Hyperbolic space